Design and modelling of planar inductor arrays and electromagnetic compatibility analysis of organic light emitting diode luminaries : doctoral thesis - Kundrata, Jurica (J. Kundrata, Fakultet elektrotehnike i računarstva, 2017)
Organic Light-Emitting Diode (OLED) luminaries are planar, diffuse light sources which are powered by DC-DC converters which may use planar inductors to achieve low profile. A number of challenges are present when designing a planar inductor. Some of the challenges stem from the inductor itself, while the other challenges are related to the OLED driver requirements, the electromagnetic compatibility (EMC) and the OLED construction. Large-area luminaries may consist of multiple OLED cells and their converters, which stresses the importance of the EMC considerations.